Water-driven modulation of multiresponsive properties in acylhydrazone-based crystals - Manoharan, Deepak; Bhowmik, Aritra; Mishra, Manish Kumar; Ghosh, Soumyajit (Chemical Communications, 2025)
A pyrene-substituted acylhydrazone (PyAc) crystal undergoes a water-driven transition from elasticity to thermoplastic bending. The hydrated crystal remains two-dimensional (2D) elastic until heating, after which it becomes brittle and bent upon dehydration. While the hydrated crystal is non-photoresponsive, the anhydrous form exhibits photomechanical bending due to favorable E-Z photoisomerization. These distinct properties, governed by solvent channels, molecular packing, and non-covalent interactions, demonstrate PyAc's potential for smart actuators and photoswitchable devices.